The Relationship between Emotional Intelligence, Organisational Commitment, Work Environment, and Reward Systems on the Performance of Educational Personnel in Private Universities in West Java - Kania Laelawati; Yudi Garnida (Universitas Mercu Buana, 2026)
Objective: Educational personnel play a strategic role in maintaining the quality of administrative and academic services in private higher education institutions (PTS). Despite their importance, empirical studies examining determinants of their performance remain limited. This study aims to analyze the influence of emotional intelligence, organizational commitment, work environment, and reward systems on the performance of educational personnel in private universities in West Java.Methodology: This study employed a quantitative approach with a causal associative design. The population consisted of permanent educational personnel across private universities in West Java. Using proportional stratified random sampling, 200 respondents were selected. Data were collected through a structured questionnaire using a five-point Likert scale and analyzed using Structural Equation Modeling–Partial Least Squares (PLS-SEM) with SmartPLS.Findings: The results show that emotional intelligence, organizational commitment, and work environment have positive and significant effects on performance. In contrast, the reward system demonstrates a significant negative effect, indicating that perceived unfairness or misalignment in reward distribution may reduce employee performance.Conclusion: This study highlights the importance of integrating psychological competencies and organizational factors in enhancing performance within private universities. While strengthening emotional capacity, commitment, and work climate is essential, institutional leaders must ensure that reward systems are transparent, fair, and performance-based to avoid demotivating effects.